Faunestic Study of the Aquatic Arthropods in a Tourism Area in Northern Iran - Mansoureh Shaeghi; Hossein Dehghan; Kamran Pakdad; Fatemeh Nikpour; Azad Absavaran; Aioub Sofizadeh; Amir Ahmad Akhavan; Hassan Vatandoost; Abbass Aghai-Afshar (Tehran University of Medical Sciences, 2017)
Background: Aquatic insects are very abundant and divers groups of insects that are associated with an aquatic or semiaquatic environment in one or more of their life stages. These insects have been, in some cases, well studied because they are vectors of several diseases. This is the first comprehensive faunistic study of aquatic insects from Babol County. The results may provide basic data for further taxonomic and ecological studies of aquatic insects as biological control agent or classification of water quality for the country. Methods: The specimens were collected using different methods including: D-frame net collector, standard mosquito dipper (350ml), Sweep-Netting and plastic pipette. Sampling carried out in different part of breading places in several times. Results: During this study a total of 196 aquatic specimens were collected from different habitats and were morphologically identified including 18 families classified in 6 orders: Diptera, Trichoptera, Ephemeroptera, Plecoptera, Hemiptera and Odonata. Babol and Amol district in Mazandaran Province are located in humid climate regions with suitable ecological factors of humidity, moderate temperature and the variety of plant species. There are different species of aquatic insects in different habitats. Conclusion: The results will provide information for biodeveristy, species richness, their role for biological control as well as calcification of rivers based on abundance of aquatic insects. Therefore the understanding of ecological specifications of aquatic insects could provide a clue for further Arthropod-borne disease control. Additionally aquatic insect could be used for classification of water bodies